Bai givim mipela planti strong : teacher training programmes and teacher empowerment in Papua New Guinea : a research report presented in partial fulfilment of the requirements for the degree of Master of International Development at Massey University, Manawatū, New Zealand - Ready, Joseph (Massey University, 2022)
Teachers are an indispensable component of an education system. “Teachers are one of the most influential and powerful forces for equity, access and quality in education and key to sustainable global development” (UNESCO, 2008b, para 1.). Issues of teaching training and retention are having significant impacts on the quality of education in countries of the Global South. The increased focus on education access have resulted in classroom sizes ballooning in Papua New Guinea which in turn has impacted the quality of education. Numerous donors and agencies are working in Papua New Guinea in the education space. Non-governmental organisations (NGOs) have been filling the gaps in teacher training through programmes to support and address the quality of education. Little is known about the extent to which teachers in these programmes are empowered. Therefore, it is timely to look at the relationship between teacher training programmes and teacher empowerment. This report uses an adapted empowerment approach as a theoretical framework to understand how teacher training programmes can empower teachers. This qualitative research draws on the case study of Kokoda Track Foundation (KTF), an education, health, and community NGO with a specific focus on the Teach for Tomorrow programmes. The project involved multiple methods to collect data, which were: tok stori, a culturally appropriate method of research with participants, document analysis, and a semi structured interview. The voices of participants feature teachers and an NGO employee with a strong localisation focus. Three key themes of culture, knowledge and partnership were identified from literature and form the foundation on which the empowerment lens was applied to this research. Findings show that there was a substantial increase in the amount of trained and certified teachers through the T4T programmes. Opportunities to improve the quality of teaching were provided through professional development and training. This received positive response from participants. Recognition of existing teacher knowledge of their communities was a vital part to ensure programme content focused on adding value to teachers’ knowledge. Overall, KTF programmes are making positive changes which empower teachers professionally, personally and as member of the community.
Keywords: 390307 Teacher education and professional development of educators; 451499 Pacific Peoples education not elsewhere classified